Long short-term memory neural network for traffic speed prediction using remote microwave sensor data - Ma, Xiaolei; Tao, Zhimin; Wang, Yinhai; Yu, Haiyang; Wang, Yunpeng (Transportation research. Part C, Emerging technologies, 2015)
•A Long Short-Term Memory Neural Network (LSTM) is developed for travel speed prediction.•The LSTM NN can capture the long-term temporal dependency for time series.•The LSTM NN can automatically determine the optimal time window.•A comparative study suggests that the LSTM NN receives the best performance. Neural networks have been extensively applied to short-term traffic prediction in the past years. This study proposes a novel architecture of neural networks, Long Short-Term Neural Network (LSTM NN), to capture nonlinear traffic dynamic in an effective manner. The LSTM NN can overcome the issue of back-propagated error decay through memory blocks, and thus exhibits the superior capability for time series prediction with long temporal dependency. In addition, the LSTM NN can automatically determine the optimal time lags. To validate the effectiveness of LSTM NN, travel speed data from traffic microwave detectors in Beijing are used for model training and testing. A comparison with different topologies of dynamic neural networks as well as other prevailing parametric and nonparametric algorithms suggests that LSTM NN can achieve the best prediction performance in terms of both accuracy and stability.